Furniture Timber and Allied Trades Union - member's contribution card, 1989 (London, 1983)
1983 1980-95 "Furniture Timber and Allied Trades Union - member's contribution card, 1989" [BW0043], 1983, Trades Union Congress Card belonging to A. Tyrrell of Hammersmith Branch.